IMPACT OF COVID-19 PANDEMIC ON MARKET SHARE AND RETURN IN CONSTRUCTION INDUSTRY - Fernando Y. Solar; Rosyida Tri Nurdyana; Velasri Vebraudia; Harry Patria (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Covid-19 pandemic has had a significant impact on all sectors and industries in Indonesia, including the construction industry. Completion of infrastructure development projects which are controlled by construction SOEs is largely hampered. The purpose of this study was to analyze the impact of Covid-19 on the market share and returns of state-owned enterprises in the construction industry compared to conditions before the pandemic. The study used stock price data in the building construction industry during the period March 2018 - 2020 and March 2020 - August 2021. The method used is Modern Portfolio Theory with Monte Carlo Simulation for portfolio optimization. The results showed that the Sharpe Ratio of the Portfolio in the period before the COVID-19 pandemic had a return around minus 4.9% to 33% and the risk was around 30.9% to 41.2%. During the pandemic, although the stock returns provided by the portfolio improved slightly, the risk increased between 53.7% to 63.3%. Therefore, the government and investors should pay more attention to selectively investing in the construction sector..